Topographical and Morphometrical Studies on the Liver in Rabbit (Oryctolagus cuniculus) - Verma, Abhinov; Pathak, Archana; Gupta, S. K.; Farooqui, M. M.; Prakash, Ajay (Indian Journal of Veterinary Anatomy, 2016)
Three clinically healthy adult rabbits were procured from the department of microbiology for the Post-Graduate teaching. The incision was given on the ventral aspect of abdominal cavity to expose the liver. The topographic location and morphology of the liver were recorded. The biometry was done and the data were statistically analysed. In rabbit, liver was present just behind the diaphragm and occupied left as well as right part of the epigastric region of abdominal cavity. It was situated between 7th to 9th intercostal space in the abdominal cavity. Left lateral lobe, left medial lobe and right lobe were associated very close to each other around esophageal notch; whereas the caudate lobe was located away from other lobes and it was attached with portal vein entering into the liver. Left lateral lobe was the largest lobe and quadrate lobe was smallest among all lobes. Gall bladder was pyriform in shape and was completely embedded on the visceral surface of right lobe and was not visible on the parietal surface of liver.